Kuno Indah dan Menawan: Kajian Semantik Penggunaan Metafora dalam Harian Kompas Online dan Pos Kota - Ienneke Indra Dewi (Humaniora, 2011)
This discussion is to disclose somewhat called as conservative language style, but obviously is really powerful; that is metaphor usage. Metaphor is assumed as conservative literature language. The article will show the usage of metaphor in everyday life, taken from Kompas online and Poskota online. The analysis willalso be about powerful and function of this language style comparing to usual language. Metaphor density in some articles will also be discussed. The result showed that by using metaphor in many writings including abstract could disclose more specific and also give specific reaction to readers. Besides, it is found that the two sources had in average one person using metaphor every 100 words.